Sugarcane Cultivars Descriptive Fact Sheet: CPCL 97-2730 and CPCL 00-4111 - Hardev Sandhu; Wayne Davidson (EDIS)
CPCL 97-2730 (Milligan et al. 2009) and CPCL 00-4111 (Glynn et al. 2011) are developed through the cooperative agreement between the United States Department of Agriculture (USDA), Canal Point, the university of Florida, Everglades Research and Education Center, Belle Glade and Florida Sugar Cane League. Prefix ‘CPCL’ in the name of these cultivars indicate that their crosses were made at the US Sugar Corporation, Clewiston (CL) and selection at different stages was carried through the cooperative breeding and selection program based at Canal Point (CP). Both are emerging sugarcane cultivars in Florida with their rapid expansion in last couple of years. CPCL 97-2730 and CPCL 00-4111 were ranked among the top 10 sugarcane cultivars in Florida in 2015 sugarcane variety census (VanWeelden et al. 2016) based on their total acreage.  High biomass yield and better rust resistance than most commercial cultivars greatly improves the chances of their adoption by the growers. The purpose of this fact sheet is to provide basic information (Table 1) and yield and disease information (Table 2) about CPCL 97-2730 and CPCL 00-4111 to assist growers in decision making on further expansion of these cultivars.